Strength enhancement of high strength steel beams by engineered cementitious composites encasement. (15th March 2020) - Kabir, Md. Imran; Lee, C.K.; Rana, Mohammad M.; Zhang, Y.X.
Highlights: ECC encasement is used to enhance the strength of high strength steel beams. Experiments and numerical study are conducted to study the enhancement effects. Test results confirmed that ECC layer crushed after the steel flange yielded. A FE model is developed to predict the flexural behaviours of the encased beams. Abstract: This study proposes a method of using Polyvinyl Alcohol Engineered Cementitious Composites (PVA-ECC) encasement to provide continuous restraints along the compression flange of High Strength Steel (HSS) section so that it will reach its sectional plastic moment resistance under bending without lateral restraint. In order to demonstrate the effectiveness of the proposed method, experimental and numerical investigations were carried out to study the flexural strength of the ECC encased HSS beams (ECC-HSS beams). Six simply supported beams fabricated with identical HSS sections but with different encasement configurations were tested until failure. Flexural resistance and failure modes of the ECC-HSS beams were compared with similar bare HSS and normal concrete (NC) encased HSS beams (NC-HSS beams). It was found that when compared with the bare HSS and NC-HSS beams, a significant enhancement in flexural resistance was achieved for the ECC-HSS beams. More importantly, this study confirmed that the compressive ECC layers was crushed after the compression flanges were yielded and therefore successfully prevented the onset of lateral torsional buckling. Besides the flexural responses, the interfacial slip behaviours along the compression flange of the HSS section were also studied. Finally, a finite element (FE) model was developed and validated against the experimental results.